1993
DOI: 10.1016/0550-3213(93)90481-4
|View full text |Cite
|
Sign up to set email alerts
|

Topological twist in four dimensions, R-duality and hyperinstantons

Abstract: ABSTRACT. In this paper we continue the programme of topologically twisting N=2 theories in D=4, focusing on the coupling of vector multiplets to N=2 supergravity. We show that in the minimal case, namely when the special geometry prepotential F (X) is a quadratic polynomial, the theory has a so far unknown on shell U (1) symmetry, that we name R-duality. R-duality is a generalization of the chiraldual on shell symmetry of N=2 pure supergravity and of the R-symmetry of N=2super Yang-Mills theory. Thanks to thi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
98
0

Year Published

1994
1994
2016
2016

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(101 citation statements)
references
References 41 publications
3
98
0
Order By: Relevance
“…In general, although the starting N=2 theory is defined on a flat world-manifold M (when supersymmetry is global), yet the final theory can be defined on any M and it is independent of the choice of the metric on M. Recently [15,16,17,18], we have shown that any N=2 globally but also locally supersymmetric theory in four dimensions can be twisted, if the topological twist is suitably improved. One gets a topological version of the theories, namely topological gravity, topological Yang-Mills theory and topological σ-model, eventually coupled together.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In general, although the starting N=2 theory is defined on a flat world-manifold M (when supersymmetry is global), yet the final theory can be defined on any M and it is independent of the choice of the metric on M. Recently [15,16,17,18], we have shown that any N=2 globally but also locally supersymmetric theory in four dimensions can be twisted, if the topological twist is suitably improved. One gets a topological version of the theories, namely topological gravity, topological Yang-Mills theory and topological σ-model, eventually coupled together.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, topological Yang-Mills theory is gauge-fixed by the equations of the usual Yang-Mills instantons. The novelty comes from the twist of the N=2 σ-model [17,18] describing the self-interaction of hypermultiplets [20,21]. The new instantons that gauge-fix this theory were called by us hyperinstantons and are the main subject of the present paper.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For this reason the maps satisfying eq. (2.28) were dubbed hyperinstantons in [22] and it was also observed that they are tri-holomorphic since eq. (2.28) can be interpreted as the statement that they are holomorphic with respect to the average of the three complex structures.…”
Section: Relation Of the Arnold-beltrami Fluxes With Hyperinstantonsmentioning
confidence: 99%
“…In this section, following once again [11] and [10] we present the general form of a rigid N = 2 supersymmetric sigma-model in D = 4 and we perform its topological twist according to the 4D-algorithm developed by Anselmi and Fré in [12], [13], [14]. Given the base flat manifold M 4 , which has always a local HyperKähler structure, supersymmetry requires that the target manifold should be a HyperKähler manifold N 4m of real dimension 4m.…”
Section: Gamma Matricesmentioning
confidence: 99%